2011
DOI: 10.1080/19942060.2011.11015367
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Numerical Schemes for Dispersed Phase Modeling of Cyclone Separators

Abstract: This study investigates the performance of different discretization schemes for simulation of dispersed phase of cyclone separators by using Reynolds stress turbulence model facility of CFD code Fluent 6.3.26. The continuous flow inside the cyclone separator is simulated by solving Reynolds averaged three dimensional unsteady Navier-Stokes equation in Eulerian reference frame whereas the dispersed phase is modeled using Lagrangian approach. Analysis of computed results shows that the high order discretization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…The earliest works showed that eddy viscosity turbulence models such as standard k-ε were incapable of accurate prediction of the swirling flow in cyclones [13] [14]. Others later reported an appropriate agreement with experimental data using a more complex Reynolds Stress turbulence model [15] [16]. Moreover, more demanding modeling with large eddy simulations (LES) was found to give an improved agreement with LDA measurements [17] [18] [19] [20] [21].…”
Section: Introductionmentioning
confidence: 85%
“…The earliest works showed that eddy viscosity turbulence models such as standard k-ε were incapable of accurate prediction of the swirling flow in cyclones [13] [14]. Others later reported an appropriate agreement with experimental data using a more complex Reynolds Stress turbulence model [15] [16]. Moreover, more demanding modeling with large eddy simulations (LES) was found to give an improved agreement with LDA measurements [17] [18] [19] [20] [21].…”
Section: Introductionmentioning
confidence: 85%
“…Spherical solid particles gets dispersed and diluted into gas phase, gas-solid interaction and influence of the dispersed particles volume fraction on gas phase are negligibly small. Generally particles loading in a cyclone is small (3-5%), the presence of particles does not affected by flow field where volume fraction occupied by dispersed second phase is less than 1% therefore one way coupling is adopted for simulation [5,16]. Interaction among the particles is neglected due to dilute flow.…”
Section: Model Equation For Particles Phasementioning
confidence: 99%
“…Geometry swirl number has influence on mean flow characteristics and maximum tangential velocity influences vortex size. Shukla et al [16] evaluated different numerical schemes for dispersed phase in cyclone separator.…”
Section: Introductionmentioning
confidence: 99%
“…The numerical and the experimental data were compared. Other authors have also used these experimental data as a basis of comparison were Zhao et al (2006); Shukla et al (2011a); Shukla et al (2011b), and Shukla et al (2013).…”
Section: Simulation Set-upmentioning
confidence: 99%
“…The drag force is considered to be the dominant force in the cyclone (Utakir et al, 2010 andShukla et al, 2011a and.…”
Section: Momentum and Mass Conservation Equationsmentioning
confidence: 99%